Chapter Regina della Scala e Bernabò Visconti. Progetti di affermazione dinastica nel dominio visconteo - Covini, Maria Nadia (Reti Medievali E-Book, 2021)
The figure of Regina della Scala, Bernabò Visconti's wife, is here reconsidered on the basis of available chronicles and documents. About her political agency, Regina was often involved by her husband in a "joint dominion" over some cities. Her strong and determined action in promoting her male sons to the detriment of her nephew and son-in-law Gian Galeazzo Visconti is emphasized. The Scaligera received from her husband, at various times, a complex of localities, funds and jurisdictions very scattered in the territory of the Visconti domain, from which she drew income and wealth. Rather than forming her own domain, Regina cultivate the project of achieving autonomy and resources to promote her and Bernabò Visconti's descendants.